The hydrogeochemical characteristics of groundwaters recharging from the Lower Miocene clastic and carbonate units around Ağın (Elâzığ) - Öztekin Okan, Özlem; Canpolat, Özgür (Gumushane University, 2022)
Ağın district is presented within the recharge basin of Keban Dam Lake. The hydrogeochemical characteristics of groundwaters of Ağın district were investigated in this study. Within the scope of the study, the origins of major anions, cations, some potentially toxic elements in groundwaters were investigated, and the hydrogeochemical features of groundwaters were compared and evaluated with the drinking water standards in Turkey and the world. The groundwaters were sampled in the rainy and the dry seasons. The aquifer formation of the groundwaters is stratified limestones of Alibonca formation and groundwaters are grouped as Ca-HCO3 and Ca-Mg-HCO3 type waters. Seasonal changes were determined in the temperature, pH, EC values, Cl-and SO4-2 contents of the groundwaters. The groundwaters are generally suitable for drinking purposes in terms of major anion, cation, Al, Cr, Cu, Fe, Mn, Pb, Zn, Ni contents. However, the groundwater of the borehole drilled close to the Keban Dam lake beach is not suitable for drinking in terms of Al (612.00 ppb), Fe (569.00 ppb) and Mn (52.1 ppb) concentrations, which are determined above the maximum limit values of drinking water standards during the rainy season. Furthermore, Cu, Cr and Zn concentrations in this borehole’ groundwater are higher compare to others during the rainy season. In general, groundwater-rock interaction is the the main factor controlling the major anion, cation, and potentially toxic element contents of the studied groundwaters. In addition, the hydrogeochemical properties of the groundwaters are also affected by anthropogenic factors such as livestock barns and the use of agricultural fertilizers. High concentrations of potentially toxic element contents determined in the borehole, especially during the rainy season, could suggest that there may be lake water intrusion from Keban Dam into the freshwater aquifer. © 2022, Gumushane University. All rights reserved.
Ağın (Elâzığ) çevresinde Alt Miyosen yaşlı kırıntılı ve karbonatlı birimlerden beslenen yeraltı sularının hidrojeokimyasal karakteristikleri
Keywords: Ağın; Groundwater-rock interaction; Hydrogeochemistry; Keban Dam Lake; Potentially toxic element